Authentic video materials for developing learners’ communicative competence (SCIENCE and SOCIETY, 2024)
In this article, the communicative competence of pupils aimed at improvement and development, its specific features, is described in a systematic and comprehensive way. Ideas and suggestions related to the successful communication are presented for developing the communicative competence in a foreign language.